Malaysian generation Y employees' leadership preference in the private sector: an exploratory qualitative study / Sharizan Sharkawi - Sharkawi, Sharizan (2018)
The current workforce in Malaysia is experiencing changing employee demographics. Generation Y, those age 34 years and below (born in 1980 - 1999), makes up nearly half of the labour force today. They are playing a vital role in the Malaysian labour market by helping to spearhead the country's future economic growth. However, a dilemma confronting leaders today is the limited understanding when leading the Gen Y and ironically the organisation's future vitality is dependent on its ability to work effectively with Gen Ys. There have been numerous feedbacks on Gen Y not staying long in organisations making job retention a challenge. Although the study of leadership has been well established over the centuries, the generational preferences of leadership particularly of the Gen Ys' have been overlooked in the research and literature of leadership studies. Thus, the main aim of this study was to explore the leadership preference of Malaysian Gen Y employees in the private sector. A qualitative approach was employed as an attempt to understand the phenomena from the Malaysian Gen Y employees' perspective. Data were gathered from ten (10) participants who were purposely selected using a criterion-based selection. In-depth semi structured interviews were conducted with the intention to obtain real life experiences of the participants. Data analysis was conducted using the grounded theory analytical procedure in which an inductive analysis strategy was employed to generate the patterns, themes, and categories derived from the data itself. Findings from this research suggest that the Malaysian Gen Y employees interviewed preferred leaders who demonstrate both transformational and servant leadership at the same time - a hybridisation of leadership theory, TransServe Model. They desire leaders with the following qualities: (i) competent and knowledgeable; (ii) give guidance and develop employees; (iii) personable and caring; (iv) trust and respectful of others; (v) provide direction; and (vi) lead by example. Contributions of this study include recommendations for leaders and HR practitioners on guidelines to managing the Gen Y employees more effectively and to the body of leadership knowledge specifically on the Generation Y Malaysian employees in the private sector workplaces.